The combustion characteristics of anthracite and pine sawdust blends. Issue 11 (3rd June 2017) - Lu, Guangjun; Zhang, Kai; Cheng, Fangqin
ABSTRACT: The combustion characteristics of anthracite, pine sawdust, and their blends were evaluated using a thermogravimetric analyzer (TGA). Pine sawdust was blended with anthracite in the range of 0–100 wt% to evaluate their combustion behavior. Pine sawdust combustion took place in two steps: between 211 and 385°C the volatiles were released and burned, and at 385–491°C char combustion takes place. In contrast, anthracite was characterized by only one combustion stage at 420–684°C. The anthracite and pine sawdust blends presented three combustion steps, corresponding to the sum of the anthracite and pine sawdust individual stages. In the blends combustion process, the temperature displacement occurred compared to anthracite and pine sawdust. There was only one meeting point, i.e., the ignition temperature, for anthracite (496°C). Ignition temperatures were 212°C for pine sawdust and 496°C for anthracite, 313, 311, and 311°C for 80:20, 70:30, and 60:40 (anthracite-to-pine sawdust mass ratio), respectively. The activation energy of blends combustion was lower compared with that of anthracite combustion. The results obtained can be explained by interaction effects when both anthracite and pine sawdust were blended in the combustion process.